Living With Parents-In-Law Increased the Risk of Postpartum Depression in Chinese Women - Peng, Songxu; Lai, Xin; Qiu, Jun; Du, Yukai; Yang, Jing; Bai, Ying; Jia, Yanhong; Meng, Liping; Wang, Kewei; Zhang, Xiangyang (Frontiers in Psychiatry, 2021)
Background：A variety of psychological and socioeconomic factors contribute to the development of postpartum depression (PPD). However, the relationship between maternal living arrangements and PPD is unclear. Objective：To assess the relationship between maternal living arrangements and PPD in Chinese population. Methods：A cross-sectional survey was conducted among puerperal women delivered in Baoan Maternal and Child Health Hospital in Shenzhen, China. The Edinburgh Postnatal Depression Scale (EPDS) was used to assess PPD. Results：A total of 4813 women were recruited, of whom 2535 (52.7%) lived only with their husbands, 664 (13.8%) lived with their parents, and 1614 (33.5%) lived with their parents-in-law. Compared with women who lived with husbands, puerperal women who lived with their parents-in-law were more likely to be positive for PPD screening (14.1% vs 10.5%, P < 0.001). After adjusting for other influencing factors, living with parents-in-law was significantly associated with the risk of PPD (OR = 1.38, 95% CI, 1.12–1.70). Additionally, stratification analyses showed that the association between living with parents-in-law and the presence of PPD was more significant in women with anxiety during pregnancy (P for interaction < 0.05). Conclusions and Relevance：Our data confirm that the maternal living arrangements affect the risk of PPD, especially among women with anxiety during pregnancy. Therefore, more targeted preventive measures should be taken for postpartum depression in women who live with their parents-in-law.